2012
DOI: 10.1073/pnas.1205184109
|View full text |Cite
|
Sign up to set email alerts
|

Thieving rodents as substitute dispersers of megafaunal seeds

Abstract: The Neotropics have many plant species that seem to be adapted for seed dispersal by megafauna that went extinct in the late Pleistocene. Given the crucial importance of seed dispersal for plant persistence, it remains a mystery how these plants have survived more than 10,000 y without their mutualist dispersers. Here we present support for the hypothesis that secondary seed dispersal by scatterhoarding rodents has facilitated the persistence of these largeseeded species. We used miniature radio transmitters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
305
2
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(322 citation statements)
references
References 57 publications
3
305
2
9
Order By: Relevance
“…Previous studies have shown that seed-caching birds and rodents respond to an increase in cache theft rates by increasing their rate of food caching (Vander Wall & Jenkins 2003;Dally et al 2006;Huang et al 2011; but see Dally et al 2006 for alternate responses to cache theft), suggesting that this information is important to hoarders. It is possible that the agoutis in our study surveyed their caches to assess theft risk, which would allow them to recover caches and move them to safer places if necessary (Hirsch et al 2012a, b;Jansen et al 2012), but whether these activities are a response to perceived theft risk is not known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that seed-caching birds and rodents respond to an increase in cache theft rates by increasing their rate of food caching (Vander Wall & Jenkins 2003;Dally et al 2006;Huang et al 2011; but see Dally et al 2006 for alternate responses to cache theft), suggesting that this information is important to hoarders. It is possible that the agoutis in our study surveyed their caches to assess theft risk, which would allow them to recover caches and move them to safer places if necessary (Hirsch et al 2012a, b;Jansen et al 2012), but whether these activities are a response to perceived theft risk is not known.…”
Section: Discussionmentioning
confidence: 99%
“…When seeds were buried, the transmitters affixed to the ends of the wire remained above ground, thus allowing us to place the transmitters on top of magnets that deactivated the transmitter and saved battery life. When the seed was moved by an agouti or other animal, the transmitter was activated, allowing us to find the new location of the seed with hand-held radiotelemetry equipment (for full details see: Hirsch et al 2012b;Jansen et al 2012). We covered the transmitter and flagging tape with loose leaf litter to reduce possible visual cues.…”
Section: Seed Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, esto dependerá de si la depredación de M. flexuosa por brúquidos ocurre antes o después de que las semillas caen de Dispersión de semillas de Mauritia flexuosa (Arecaceae) por frugívoros terrestres en Laguna Azul, Beni, Bolivia ACTA AMAZONICA los árboles. Si los brúquidos ovipositan antes de la caída de los frutos, como en el caso de Astrocaryum standleyanum (Jansen et al 2012), el efecto será insignificante.…”
Section: Discussionunclassified
“…Este comportamiento de acopio esparcido o "scatterhoarding" (Morris 1962) cumple un rol importante en la dispersión de las semillas (Alho 1982;Jansen et al 2004;Jorge y Howe 2009). Jansen et al (2012) reportan que un 14% de las semillas enterradas por D. punctata sobreviven un año; y las semillas enterradas suelen germinar más rápido que las que no se entierran (Forget y Milleron 1991). Dasyprocta dispersa varios géneros de palmeras: Acrocomia, Astrocaryum, Attalea, Mauritia, Oenocarpus, Phytelephas y Syagrus (Silvius y Fragoso 2003;Pires y Galetti 2012;Emsens et al 2013).…”
unclassified